Adult Education, Assessment and the Beginnings of the GED - Amy D. Rose (Adult Education Research Conference, 2006)
This study examines the development and implementation of the General Educational Development (GED) examination in the United States. It examines the ways that the GED was initially conceptualized and how the notion of equivalence was popularized.
Keywords: History; General Educational Development (GED); adult education; testing